Jenny Cooper has a secret : a novel - Fielding, Joy (Ballantine Books, 2025)
In this riveting psychological thriller from the New York Times bestselling author of All the Wrong Places, a dementia patient reveals a deadly secret--and one woman must decide whether to believe her. Reeling from her husband's death and best friend's dementia diagnosis, seventy-six-year-old Linda Davidson feels lost and alone. Her beloved daughter Kleo and son-in-law Mick have moved into her house to keep her company, but the constant bickering quickly turns their presence into yet another worry on Linda's long list. Eager to escape the tension at home, Linda goes to visit her friend at Legacy Place, a memory care facility for the elderly, where she meets Jenny Cooper, a ninety-two-year-old dementia patient who makes a shocking confession: she kills people. Linda dismisses the so-called secret as the confusion of an ailing mind, but Jenny seems strangely lucid during their visits as she recounts stories of her many victims--mostly men who hurt her. Then a fellow patient at Legacy Place dies. Everyone else sees it as the natural death of an sick old man, but Linda can't help but wonder: is there any chance Jenny's telling the truth?